A atuação do coordenador pedagógico no espaço escolar: desafios e possibilidades - MARQUES, Patricia de Oliveira (2019)
The proposed study aims to understand the activities of the Pedagogical Coordinator in the educational scenario. The methodology developed from a qualitative approach and a bibliographic survey. In that sense, I prioritized the authors: Paro (2001); Lima (2002); Lima and Santos (2007); Serpa (2011), among others, in which it was worked throughout the course of pedagogy, gave us support for understanding the subject dealt with. In the course of the research I realized that the educational management is not done alone, it is necessary mechanisms for its proper functioning, among these mechanisms I emphasize the importance of continuing training for the pedagogical coordinator to have not only the knowledge of their functions, but also the recognition of their identity in the school environment.